Implementasi sistem e-filing, e-billing, dan pemahaman perpajakan terhadap kepatuhan wajib pajak di Tasikmalaya - Lamdora, Raden Agil; Suyono, Eko (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to determine: (1) Implementation of e-filing, e-billing system, taxation understanding, and taxpayer compliance at the KPP Pratama Tasikmalaya. (2) The effect of the implementing of e-filing, e-billing and taxation understanding on taxpayer compliance at the Pratama Tasikmalaya tax service office. This study uses primary data by distributing online questionnaires its aimed at taxpayers who meet the criteria determined by the researcher. The population in this study are taxpayers who are registered as e-filing and ebilling taxpayers at the Pratama tax service office in Tasikmalaya. In this study using a sample of 100 respondents, the sampling method uses self-selected respondents, is someone who chooses himself to participate becomes a respondent voluntarily of his own volition because of interest in the research being conducted. The analysis technique used to manage the data was multiple regression tests using the SPSS program. The results of this study indicate that (1) Implementation of e-filing, e-billing system, taxation understanding, and taxpayer compliance at the KPP Pratama Tasikmalaya showed a good condition. (2) The implementation of e-filing and e-billing system partially does not affect on taxpayer compliance. (3) Taxation understanding partially has a significant affect on taxpayer compliance